2019
DOI: 10.1109/access.2019.2930585
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Delay Calibration Method for Profile Estimation of Two-Layered Rough Surfaces

Abstract: For detection of a two-layered rough surface structure through ground-penetrating radar, the estimation of the profile of each layered rough surface is an important problem to be solved. In modeling and calculating the scattering of two-layered rough surfaces, we found that the profile of the upper rough surface can be observed directly through the figure of the echo from the upper surface. However, the echo of the lower rough surface has a quite different shape from its surface profile, because of the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These classes of approaches, although more computationally expensive, are particularly advantageous when certain geometric configurations and specific soils are present in the domain. In addition, several radar-like techniques [ 37 , 38 , 39 , 40 ] have been recently proposed in this research area to allow soil profiling, so that retrieved soil configuration can be accurately integrated into the electromagnetic model as a priori information [ 41 ]. Finally, hybrid solutions combining analytical and numerical models have also been proposed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These classes of approaches, although more computationally expensive, are particularly advantageous when certain geometric configurations and specific soils are present in the domain. In addition, several radar-like techniques [ 37 , 38 , 39 , 40 ] have been recently proposed in this research area to allow soil profiling, so that retrieved soil configuration can be accurately integrated into the electromagnetic model as a priori information [ 41 ]. Finally, hybrid solutions combining analytical and numerical models have also been proposed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the rough surface contour can eliminate clutter interference from the target, allowing more accurate target identification and imaging. Scattering from rough surfaces with laminar structures has been calculated using the method of Finite Difference Time Domain (FDTD) [19,20]. It was found that the shape of the echo of the upper surface was always the same as the contour of the rough surface, regardless of the change in roughness.…”
Section: Introductionmentioning
confidence: 99%